2018
DOI: 10.5812/aapm.74355
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Dexmedetomidine as an Adjuvant to Lidocaine in Forearm Fracture Surgeries by Supraclavicular Block Procedure Under Ultrasound-Guided

Abstract: BackgroundTo improve the brachial plexus block (BPB) performance, different compounds have been used as adjuvants to local analgesics.ObjectivesThe aim of the present study was to investigate the effects of adding DEX to lidocaine on effectiveness of nerve block, and postoperative pain in forearm fracture surgery by supraclavicular BPB undergoing ultrasound-guided.MethodsThis was a double-blinded randomized clinical trial conducted on 72 patients with ASA classes I and II, which were candidates for forearm fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…In some studies, adding dexmedetomidine as an adjuvant to opioids or local anesthetics led to prolonged intraoperative analgesia, more postoperative pain relief, less nausea and vomiting, and fewer hemodynamic changes ( 26 - 28 ). In a study of pain management after caesarean section, adding dexmedetomidine to sufentanil decreased opioid consumption and increased patient satisfaction ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, adding dexmedetomidine as an adjuvant to opioids or local anesthetics led to prolonged intraoperative analgesia, more postoperative pain relief, less nausea and vomiting, and fewer hemodynamic changes ( 26 - 28 ). In a study of pain management after caesarean section, adding dexmedetomidine to sufentanil decreased opioid consumption and increased patient satisfaction ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adding dexmedetomidine as an adjuvant to paravertebral and supraclavicular blocks has caused better analgesia and lower postoperative analgesic consumption (27, 28). In a study, Bajwa et al administered dexmedetomidine, as an adjunct in epidural anesthesia, and reported its better effects compared to clonidine; it also improved patients’ comfort, cardiovascular parameters, and analgesia during the surgery and post-surgery (29).…”
Section: Discussionmentioning
confidence: 99%
“…The half-life of dexmedetomidine is 2.3 hours and its distribution half-life is less than 5 minutes; so, its clinical effects are very rapid ( 6 - 8 ). Also, it assists hemodynamic stability by its sympatholytic action, which has been used as a safe adjuvant during anesthesia in many clinical applications ( 9 - 12 ). Dexmedetomidine has been used as a sedative and hypnotic in procedures that do not need tracheal intubation.…”
Section: Introductionmentioning
confidence: 99%